2017
DOI: 10.1002/aet2.10030
|View full text |Cite
|
Sign up to set email alerts
|

Women in Emergency Medicine Residency Programs: An Analysis of Data From Accreditation Council for Graduate Medical Education–approved Residency Programs

Abstract: Objective: Understanding the factors associated with attracting women to a residency program would help residency program leadership build programs that are appealing to women candidates. The objective of this study was to identify factors associated with the percentage of women residents in emergency medicine (EM) residency programs.Methods: A list of 161 Accreditation Council for Graduate Medical Education-approved EM residencies was compiled. The public websites for each of the residencies was queried for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…This may be because of the fast-paced and intense nature of EM (Choo 2017); however, EM’s emergence out of military field medicine (Goniewicz 2013), with its highly masculinized culture (Braswell and Kushner 2012), likely also contributes. As might be expected based on these traits, EM has lower levels of gender parity compared with most other medical specialties (Lautenberger et al 2014): women comprise 48 percent of residents and 38 percent of medical faculty (attendings in academic or university-affiliated hospitals, rather than “community” hospitals) in medicine as a whole, but they represent only 38 percent of all EM residents (DeFazio et al 2017) and 28 percent of EM faculty (Bennett et al 2019). 2…”
Section: Literature Reviewmentioning
confidence: 93%
“…This may be because of the fast-paced and intense nature of EM (Choo 2017); however, EM’s emergence out of military field medicine (Goniewicz 2013), with its highly masculinized culture (Braswell and Kushner 2012), likely also contributes. As might be expected based on these traits, EM has lower levels of gender parity compared with most other medical specialties (Lautenberger et al 2014): women comprise 48 percent of residents and 38 percent of medical faculty (attendings in academic or university-affiliated hospitals, rather than “community” hospitals) in medicine as a whole, but they represent only 38 percent of all EM residents (DeFazio et al 2017) and 28 percent of EM faculty (Bennett et al 2019). 2…”
Section: Literature Reviewmentioning
confidence: 93%
“…Currently, 38% of emergency medicine (EM) residents and 35% of academic EM physicians are female . There are no studies evaluating the extent to which gender influences how EM residents perceive the experience of acquiring the skills required to lead resuscitations in the emergency department (ED).…”
mentioning
confidence: 99%
“…Although females now make up more than half of medical school graduates, they compose only approximately one-third of emergency medicine (EM) residents [ 1 , 2 ]. It is unclear why fewer females choose to pursue EM than males.…”
Section: Introductionmentioning
confidence: 99%
“…Although one could assume that female students may be more likely to attend an EM program with a higher proportion of female faculty, a study found that there was no correlation between the presence of women in leadership roles and the percentage of female residents in a program [ 1 ]. Still, women are the minority in academic medicine, with only 9.3% of the chair and 25.9% of the program director (PD) positions being held by women [ 1 ]. The presence of other female core faculty may have more influence on an applicant’s decision to choose a program.…”
Section: Introductionmentioning
confidence: 99%